GE_GERICHTE C/22769/2016 vom 25. Juli 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; OBLIGATION D'ENTRETIEN ; CONJOINT ; ENFANT ; REVENU ; PARTICIPATION AU CAPITAL | CC.285; CC.285.al2; LIFD.129